Dyscalculia and Attention Deficit Subtypes - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The association of specific academic deficits with attention deficit disorder (ADD) subtypes was determined in 20 students (ages 8-12) with ADD with hyperactivity (ADD/H) compared to 20 with ADD without hyperactivity (ADD/noH), at the Department of Educational Psychology, University of Texas at Austin, TX.